Healing for Adolescents: An Art-based Approach to Coping with Trauma - Vaughan, Rebecca (My University, 2017)
The purpose of this paper was to determine whether art therapy groups for middle school students dealing with trauma was beneficial or not. The students were given different materials and a different intervention each session to complete. All the interventions were geared towards trauma. At the beginning of each session was a short group intervention, then into an individual intervention. At the end of each session, everyone would gather together and share their pieces if they wished. I will be exploring what may cause trauma, and what it is and various art therapy interventions to use with children dealing with trauma. Additionally, I will address the inquiry: does group art therapy work well at this school? By exploring these topics, I will show you how art therapy interventions were beneficial to middle schoolers in groups I facilitated. The group included students ages 11-13, who experienced traumatic events in their lives. These events could include: a loss of a family member, witness of a death, involvement of drugs/alcohol in the home, family or friends, physical or mental abuse, etc.
Keywords: school; interventions; Art Therapy; trauma; adolescents; children; Visual Arts